Gene x environment interactions impact endometrial function and the menstrual cycle: PROGINS, life history, anthropometry, and physical activity. Issue 5 (1st August 2013) - Rowe, Elizabeth J.; Eisenstein, Toby K.; Meissler, Joseph; Rockwell, L. Christie
<x xml:space="preserve">Abstract</x> Objectives We assessed the impact of a high frequency, functionally significant allelic variant of the progesterone receptor gene (PROGINS) on endometrial function and menstrual cycle characteristics. Further we asked whether PROGINS moderates the impact of life history characteristics, anthropometric measures, and physical activity on endometrial function. Methods Fifty‐two women were genotyped for the PROGINS variant, provided life history information, and had anthropometric measurements made. Women monitored their menstrual bleeding for three cycles, performed mid‐cycle urinary ovulation tests, and recorded physical activity. A subset of women provided daily saliva samples and had mid‐luteal endometrial thickness measurements taken during the third menstrual cycle. Salivary progesterone was assayed using ELISAs. The direct impact of PROGINS on endometrial and menstrual cycle characteristics was determined via independent t‐tests with Bonferroni correction. Interactions between PROGINS and covariates were assessed by moderated regression. Results PROGINS did not directly impact any indicator of endometrial function. However, PROGINS caused an increase in menstrual cycle length with increasing mid‐luteal progesterone levels; the opposite relationship was present in noncarriers (P < 0.05). Additionally, PROGINS interacted with four of six anthropometric measures (BMI, waist circumference, height, and waist‐hip ratio) to impact endometrial function, however, interactions between PROGINS and life history variables, or physical activity was limited. Conclusions The gene x environment interactions we report suggest that PROGINS alters endometrial sensitivity to maternal energetic condition. Thus, the possibility of genetically‐based variation in sensitivity to energetic stress should be considered in future adaptive models of women's reproduction. Am. J. Hum. Biol. 25:681–694, 2013. © 2013 Wiley Periodicals, Inc.